Jewelry and manufacturing method thereof
Austenitic stainless steel accessories with controlled composition and microstructure address the degradation of specularity and corrosion resistance in high Cr and Mo materials by limiting intermetallic compounds, achieving superior corrosion resistance and mirror finish.
Patent Information
- Application Number
- JP2020185320
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-11-05
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-11-05
AI Technical Summary
Accessories made from materials with high Cr and Mo content face issues with intermetallic compounds that degrade specularity and corrosion resistance due to the formation of phases different from the matrix, reducing the effectiveness of these properties.
Austenitic stainless steel accessories with controlled chemical composition and microstructure, including specific limits on elements like C, Si, Mn, P, S, O, Ni, Mo, and Cr, and defined intermetallic compound sizes and distribution, combined with heat treatment and plastic working processes to maintain high corrosion resistance and specularity.
The solution provides accessories with excellent corrosion resistance and mirror finish by minimizing intermetallic compounds, ensuring the matrix maintains optimal Cr and Mo content and microstructural integrity.
Smart Images

Figure 0007605616000006 
Figure 0007605616000001 
Figure 0007605616000002
Abstract
Description
[Technical field]
[0001] The present invention relates to jewelry and a method for manufacturing jewelry. [Background technology]
[0002] 2. Description of the Related Art In recent years, some accessories to be worn, such as wristwatches, necklaces, brooches, earrings, etc., are made of stainless steel, as disclosed in Patent Document 1, for example.
[0003] On the other hand, the demand for corrosion resistance of jewelry is increasing. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-168407 A Summary of the Invention [Problem to be solved by the invention]
[0005] One method for improving the corrosion resistance of jewelry is to manufacture the jewelry from a material that contains a lot of Cr and Mo. On the other hand, when jewelry is manufactured from a material that contains a lot of Cr and Mo, high-Cr, high-Mo compounds remain in the cross section of the material that contains a lot of Cr and Mo. Since the high-Cr, high-Mo compounds are a different phase from the parent phase, there is a problem that they deteriorate the specularity of the jewelry. In addition, since the high-Cr, high-Mo compounds reduce the Cr and Mo content of the parent phase, there is a problem that they deteriorate the corrosion resistance of the jewelry.
[0006] The present invention has been made to solve the above problems, and has an object to provide an ornament having excellent corrosion resistance and specular surface properties, and a method for manufacturing the ornament. [Means for solving the problem]
[0007] (1) Chemical composition, in mass percent: C: 0.10% or less, Si: 1.5% or less, Mn: 1.5% or less, P: 0.050% or less, S: 0.050% or less, O: 0.020% or less, Ni: 15.0-38.0%, Cr: 17.0-27.0%, Mo: 4.0-8.0%, Cu: 3.0% or less, and N: Contains 0.55% or less, The balance includes Fe and impurities. The structure is austenite at 95% or more by area%, When the size of the intermetallic compound is defined as the diameter of a circle having the smallest area that can contain one intermetallic compound therein, the number of the intermetallic compounds having a size of 150 μm or more on the exposed surface of the jewelry is 0, and the number of the intermetallic compounds having a size of 13 μm or more and less than 150 μm is 3 or less, The average equivalent circular diameter of the austenite is 150 μm or less, The PRE defined by the following formula (1) is 40 or more. An ornament characterized by the above. PRE=[Cr]+3.3[Mo]+16[N]···(1) In the formula (1), [Cr], [Mo], and [N] refer to the mass% content of Cr, Mo, and N in the composition of the jewelry, and 0 is substituted if they are not contained. (2) The chemical composition further comprises, in mass %, Al: 0.001 to 0.10%, Co: 0.001 to 3.0%, W: 0.001 to 8.0%, Ta: 0.001 to 1.0%, Sn: 0.001 to 1.0%, Sb: 0.001 to 1.0%, Ga: 0.001 to 1.0%, Ti: 0.001 to 1.0%, V: 0.001 to 1.0%, Nb: 0.001 to 1.0%, Zr: 0.001 to 1.0%, Te: 0.001 to 1.0%, Se: 0.001-1.0%, B: 0.0001~0.01%, Ca: 0.0001-0.05%, Mg: 0.0001 to 0.05%, and Rare earth elements: 0.001~1.0% Contains one or more selected from The ornament described in (1) is characterized in that (3) The accessory is a watch case. The accessory described in (1) or (2) is characterized in that (4) A method for manufacturing the accessory according to any one of (1) to (3), A step of manufacturing a plate material; A heat treatment step of heat treating the plate material; A cold rolling process for plastically processing the plate material, In the heat treatment step, the heat treatment temperature is 1350 to 1600K, and the heat treatment time satisfies the following formula (2), In the cold rolling process, the reduction ratio is 7 to 50%. A method for manufacturing a personal accessory, comprising the steps of: t dif ≧(6869 / T dif -4.3326) × λ 2 (2) However, in equation (2), T dif is the heat treatment temperature (K), t dif represents the heat treatment time (hours), and λ represents the thickness of the plate material (mm). (5) A method for manufacturing the accessory according to any one of (1) to (3), Manufacturing a bar stock; a heat treatment step of heat treating the bar material; A cold wire drawing process for plastically working the bar material, In the heat treatment step, the heat treatment temperature is 1350 to 1600K, and the heat treatment time satisfies the following formula (3), In the cold drawing process, the reduction in area is 7 to 50%. A method for manufacturing a personal accessory, comprising the steps of: t dif ≧(6869 / T dif -4.3326) × d (3) However, in equation (3), T dif is the heat treatment temperature (K), t dif represents the heat treatment time (hours), and d represents the circle-equivalent diameter (mm) of the bar. (6) A method for manufacturing the accessory according to any one of (1) to (3), A step of producing a plate or bar material; a heat treatment step of heat treating the plate material or the bar material; a hot forging step of hot forging the plate material or the bar material; A cold forging process for cold forging the plate material or the bar material. In the heat treatment step, the heat treatment temperature is 1350 to 1600K; In the case of the plate material, the heat treatment time satisfies formula (2), and In the case of the bar material, the heat treatment time satisfies the formula (3). A method for manufacturing a personal accessory, comprising the steps of: t dif ≧(6869 / T dif -4.3326) × λ 2 (2) t dif ≧(6869 / T dif -4.3326) × d (3) However, in equation (2), T dif is the heat treatment temperature (K), t dif is the heat treatment time (hours), λ is the plate thickness (mm), and in equation (3), T dif is the heat treatment temperature (K), t dif represents the heat treatment time (hours), and d represents the circle-equivalent diameter (mm) of the bar. Effect of the Invention
[0008] According to the present invention, it is possible to provide an ornament having excellent corrosion resistance and specular surface properties, and a method for manufacturing the ornament. [Brief description of the drawings]
[0009] [Figure 1] 1 is an external view of an accessory according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present inventors have conducted various studies to improve the corrosion resistance and specularity of accessories, and have come to the following findings. Commercially available materials with a PRE of 40 or more contain many intermetallic compounds in their cross sections. Intermetallic compounds are defined as those having a Cr and Mo content higher than that of the matrix. When a material containing a large amount of intermetallic compounds and having a PRE of 40 or more is polished, the intermetallic compounds appear as a different phase, making it impossible to obtain a mirror surface suitable for use in jewelry. In addition, the intermetallic compounds reduce the Cr and Mo content of the parent phase, so the exposed surface of the intermetallic compounds cannot exhibit excellent corrosion resistance.
[0011] The present invention has been made as a result of the above-mentioned investigations, and the reasons for limiting the characteristic technical requirements and preferred aspects of the embodiments of the present invention will be described below. First, an ornament according to one embodiment of the present invention will be described.
[0012] (Composition of jewelry) The chemical components contained in the accessory according to one embodiment of the present invention (hereinafter, sometimes abbreviated as "accessory") and the reasons for limiting the content of each component will be described. In the following description, "%" means "mass %" unless otherwise specified.
[0013] C: 0.10% or less The C content must be 0.10% or less. If the C content exceeds 0.10%, Cr carbide is formed excessively, and the corrosion resistance of the jewelry is deteriorated. The upper limit of the C content is preferably 0.08% or less, more preferably 0.05% or less. On the other hand, C is an element that forms austenite, so it may be contained. The lower limit of the C content is preferably 0.005% or more, more preferably 0.010% or more.
[0014] Si: 1.5% or less The Si content must be 1.5% or less. If the Si content exceeds 1.5%, the precipitation of intermetallic compounds is promoted, and the corrosion resistance and specularity of the jewelry deteriorate. The upper limit of the Si content is preferably 1.0% or less, more preferably 0.6% or less. On the other hand, since Si is an element that has a deoxidizing effect, it may be contained. The lower limit of the Si content is preferably 0.10% or more, more preferably 0.30% or more.
[0015] Mn: 1.5% or less The Mn content must be 1.5% or less. If the Mn content exceeds 1.5%, the corrosion resistance of the jewelry deteriorates. The upper limit of the Mn content is preferably 1.0% or less, more preferably 0.8% or less. On the other hand, Mn is an element that forms austenite and has a deoxidizing effect, so it may be contained. The lower limit of the Mn content is preferably 0.01% or more, more preferably 0.10% or more.
[0016] P:0.050% or less The P content must be kept at 0.050% or less. If the P content exceeds 0.050%, the toughness of the jewelry deteriorates. The upper limit of the P content is preferably 0.045% or less, and more preferably 0.035% or less.
[0017] S: 0.050% or less The S content must be kept at 0.050% or less. If the S content exceeds 0.050%, the toughness and corrosion resistance of the jewelry deteriorate. The upper limit of the S content is preferably 0.040% or less, and more preferably 0.015% or less.
[0018] O: 0.020% or less The O content must be kept at 0.020% or less. If the O content exceeds 0.020%, the toughness of the jewelry deteriorates. The upper limit of the O content is preferably 0.015% or less, and more preferably 0.010% or less.
[0019] Ni: 15.0~38.0% The Ni content must be 15.0-38.0%. If the Ni content is less than 15.0%, ferrite is formed excessively, and the toughness and corrosion resistance of the jewelry deteriorate. The lower limit of the Ni content is preferably 17.0% or more, and more preferably 18.0% or more. On the other hand, if the Ni content exceeds 38.0%, the effect of improving the corrosion resistance of the jewelry is saturated. In addition, the Ni content becomes excessively high, and the jewelry becomes expensive. The upper limit of the Ni content is preferably 30.0% or less, and more preferably 20.0% or less.
[0020] Cr: 17.0~27.0% The Cr content must be 17.0-27.0%. If the Cr content is less than 17.0%, the corrosion resistance of the jewelry deteriorates. The lower limit of the Cr content is preferably 18.0% or more, more preferably 19.0% or more. On the other hand, if the Cr content exceeds 27.0%, ferrite and intermetallic compounds are excessively formed, and the toughness and corrosion resistance of the jewelry deteriorates. The upper limit of the Cr content is preferably 25.0% or less, more preferably 21.0% or less.
[0021] Mo: 4.0-8.0% The Mo content must be 4.0-8.0%. If the Mo content is less than 4.0%, the corrosion resistance of the jewelry deteriorates. The lower limit of the Mo content is preferably 5.0% or more, more preferably 6.0% or more. On the other hand, if the Mo content exceeds 8.0%, ferrite and intermetallic compounds are formed excessively, and the toughness and corrosion resistance of the jewelry deteriorates. The upper limit of the Mo content is preferably 7.5% or less, more preferably 7.0% or less.
[0022] Cu:3.0% or less The Cu content must be 3.0% or less. If the Cu content exceeds 3.0%, cracks are likely to occur during casting. The upper limit of the Cu content is preferably 1.0% or less, more preferably 0.8% or less. On the other hand, Cu may be contained since it has the effect of suppressing the progress of corrosion when corrosion occurs. The lower limit of the Cu content is preferably 0.01% or more, more preferably 0.10% or more.
[0023] N: 0.55% or less The N content must be 0.55% or less. If the N content exceeds 0.55%, cracks are likely to occur during casting. The upper limit of the N content is preferably 0.50% or less, more preferably 0.35% or less, and even more preferably 0.25% or less. On the other hand, N may be contained since it has the effect of improving corrosion resistance and forming austenite. The lower limit of the N content is preferably 0.05% or more, more preferably 0.10% or more, and even more preferably 0.15% or more.
[0024] PRE is 40 or more The PRE defined by the following formula (1) must be at least 40. If the PRE is less than 40, the corrosion resistance of the jewelry deteriorates. PRE=[Cr]+3.3[Mo]+16[N]···(1) In the formula (1), [Cr], [Mo], and [N] refer to the mass% content of Cr, Mo, and N in the composition of the jewelry, and 0 is substituted if they are not contained.
[0025] The accessory according to the present embodiment may further contain, in mass %, one or more elements selected from Al, Co, W, Ta, Sn, Sb, Ga, Ti, V, Nb, Zr, Te, Se, B, Ca, Mg, and rare earth elements in addition to the above-mentioned elements. Note that these elements do not have to be contained, so the lower limit of the content is 0.
[0026] Al: 0.10% or less The jewelry according to this embodiment may contain 0.10% or less Al. Since Al is an element having a deoxidizing effect, it may be contained. In order to obtain this effect, the content of Al when it is contained is 0.001% or more, more preferably 0.005% or more. On the other hand, if the Al content exceeds 0.10%, Al nitrides and Al oxides are formed in excess, and the corrosion resistance and toughness of the jewelry deteriorate. The upper limit of the Al content is preferably 0.05% or less, more preferably 0.02% or less.
[0027] Co:3.0% or less The jewelry according to the present embodiment may contain 3.0% or less Co. Co may be contained since it has the effect of forming austenite and suppressing the formation of intermetallic compounds. In order to obtain this effect, the content of Co when contained is 0.001% or more, more preferably 0.1% or more. On the other hand, if the Co content exceeds 3.0%, the workability is deteriorated. The upper limit of the Co content is preferably 2.0% or less, more preferably 1.5% or less.
[0028] W: 8.0% or less The accessory according to the present embodiment may contain 8.0% or less W. W may be contained since it has the effect of improving corrosion resistance. In order to obtain this effect, the content of W when contained is 0.001% or more, more preferably 0.1% or more. On the other hand, if the W content exceeds 8.0%, the workability is deteriorated. The upper limit of the W content is preferably 5.0% or less, more preferably 1.0% or less.
[0029] Ta: 1.0% or less The accessory according to the present embodiment may contain 1.0% or less Ta. Ta may be contained since it has the effect of refining crystal grains and the effect of improving corrosion resistance. In order to obtain these effects, the content of Ta when contained is 0.001% or more, more preferably 0.005% or more. On the other hand, if the Ta content exceeds 1.0%, the workability deteriorates. The upper limit of the Ta content is preferably 0.5% or less, more preferably 0.1% or less.
[0030] Sn: 1.0% or less The jewelry according to this embodiment may contain 1.0% or less Sn. Sn may be contained because it has the effect of improving corrosion resistance. In order to obtain this effect, the content of Sn when contained is 0.001% or more, more preferably 0.005% or more. On the other hand, if the Sn content exceeds 1.0%, the workability is deteriorated. The upper limit of the Sn content is preferably 0.5% or less, more preferably 0.3% or less.
[0031] Sb: 1.0% or less The jewelry according to the present embodiment may contain 1.0% or less Sb. Sb may be contained since it has the effect of improving corrosion resistance. In order to obtain this effect, the content of Sb when contained is 0.001% or more, more preferably 0.005% or more. On the other hand, if the Sb content exceeds 1.0%, the workability deteriorates. The upper limit of the Sb content is preferably 0.5% or less, more preferably 0.3% or less.
[0032] Ga: 1.0% or less The accessory according to the present embodiment may contain 1.0% or less Ga. Ga may be contained since it has the effect of improving corrosion resistance and workability. In order to obtain this effect, the content of Ga when contained is 0.001% or more, more preferably 0.015% or more. On the other hand, when the Ga content exceeds 1.0%, the effect of improving corrosion resistance and the effect of improving workability are saturated. The upper limit of the Ga content is preferably 0.5% or less, more preferably 0.3% or less.
[0033] Ti: 1.0% or less The accessory according to the present embodiment may contain 1.0% or less Ti. Ti may be contained since it has the effect of improving corrosion resistance by fixing C and N as carbonitrides and the effect of refining crystal grains. In order to obtain this effect, the content of Ti when contained is 0.001% or more, more preferably 0.01% or more. On the other hand, if the Ti content exceeds 1.0%, excessive amounts of oxides and nitrides are formed, deteriorating the workability. The upper limit of the Ti content is preferably 0.5% or less, more preferably 0.3% or less.
[0034] V: 1.0% or less The accessory according to the present embodiment may contain 1.0% or less of V. V may be contained since it has the effect of improving corrosion resistance by fixing C and N as carbonitrides and the effect of refining crystal grains. In order to obtain these effects, the content of V when contained is 0.001% or more, more preferably 0.02% or more. On the other hand, if the V content exceeds 1.0%, excessive amounts of oxides and nitrides are formed, deteriorating the workability. The upper limit of the V content is preferably 0.9% or less, more preferably 0.5% or less.
[0035] Nb: 1.0% or less The accessory according to the present embodiment may contain 1.0% or less Nb. Nb may be contained because it has the effect of fixing C and N as carbonitrides to improve corrosion resistance and the effect of refining crystal grains. In order to obtain these effects, the content of Nb when contained is 0.001% or more, more preferably 0.02% or more. On the other hand, if the Nb content exceeds 1.0%, excessive amounts of oxides and nitrides are formed, deteriorating the workability. The upper limit of the Nb content is preferably 0.5% or less, more preferably 0.2% or less.
[0036] Zr: 1.0% or less The accessory according to the present embodiment may contain 1.0% or less Zr. Zr may be contained since it has the effect of improving strength and refining crystal grains. In order to obtain these effects, the content of Zr when contained is 0.001% or more, more preferably 0.02% or more. On the other hand, if the Zr content exceeds 1.0%, the workability is deteriorated. The upper limit of the Zr content is preferably 0.5% or less, more preferably 0.2% or less.
[0037] Te: 1.0% or less The jewelry according to the present embodiment may contain 1.0% or less of Te. Te may be contained since it has the effect of improving machinability. In order to obtain this effect, the content of Te when contained is 0.001% or more, more preferably 0.01% or more. On the other hand, if the Te content exceeds 1.0%, the corrosion resistance deteriorates. The upper limit of the Te content is preferably 0.05% or less, more preferably 0.02% or less.
[0038] Se: 1.0% or less The jewelry according to the present embodiment may contain 1.0% or less Se. Se has the effect of improving machinability, so it may be contained. In order to obtain this effect, the content of Se when contained is 0.001% or more, more preferably 0.01% or more. On the other hand, if the Se content exceeds 1.0%, the corrosion resistance deteriorates. The upper limit of the Se content is preferably 0.2% or less, more preferably 0.1% or less.
[0039] B: 0.01% or less The jewelry according to this embodiment may contain 0.01% or less of B. B may be contained since it has the effect of improving hot workability. In order to obtain this effect, the content of B when contained is 0.0001% or more, more preferably 0.0005% or more. On the other hand, if the B content exceeds 0.01%, the corrosion resistance is deteriorated. The upper limit of the B content is preferably 0.005% or less, more preferably 0.003% or less.
[0040] Ca: 0.05% or less The jewelry according to the present embodiment may contain 0.05% or less Ca. Ca may be contained since it has the effect of improving hot workability. In order to obtain this effect, the content of Ca when contained is 0.0001% or more, more preferably 0.0005% or more. On the other hand, if the Ca content exceeds 0.05%, the hot workability is deteriorated. The upper limit of the Ca content is preferably 0.005% or less, more preferably 0.003% or less.
[0041] Mg: 0.05% or less The jewelry according to the present embodiment may contain 0.05% or less of Mg. Mg may be contained since it has the effect of improving hot workability. In order to obtain this effect, the content of Mg when contained is 0.0001% or more, more preferably 0.0005% or more. On the other hand, if the Mg content exceeds 0.05%, the hot workability is rather deteriorated. The upper limit of the Mg content is preferably 0.005% or less, more preferably 0.003% or less.
[0042] Rare earth elements: 1.0% or less The jewelry according to the present embodiment may contain 1.0% or less of rare earth elements. Rare earth elements may be contained because they have the effect of improving hot workability. In order to obtain this effect, the content of rare earth elements when contained is 0.001% or more, more preferably 0.005% or more. On the other hand, if the rare earth element content exceeds 1.0%, the hot workability is rather deteriorated. The upper limit of the rare earth element content is preferably 0.1% or less, more preferably 0.03% or less.
[0043] The balance includes Fe and impurities. The balance other than the above-mentioned elements includes Fe and impurities. In addition to the above-mentioned elements, other elements may be contained within a range that does not impair the effects of this embodiment. The balance other than the above-mentioned elements is preferably composed of Fe and impurities.
[0044] The method for measuring the chemical composition of jewelry is as follows. For elements other than O and N, first, samples are taken from 1 / 4 of the plate thickness for plate material. For bar material, samples are taken from 1 / 2 the length of the line segment connecting the surface and center. After that, the chemical composition is measured in accordance with JIS G 1256 (Method for fluorescent X-ray analysis of iron and steel) of 2013. In addition, O is measured for the above samples using JIS G 1239 (inert gas fusion-infrared absorption method) of 2014. N is measured for the above samples using JIS G 1228 (iron and steel-nitrogen determination method) of 2006. The shape of the plate material shall conform to the provisions of JIS G 4304 (hot-rolled stainless steel plate and strip) of 2012 or JIS G 4305 (cold-rolled stainless steel plate and strip) of 2012. Furthermore, the shape of the bar shall conform to the provisions set forth in JIS G 4303 (Stainless steel bars), 2012.
[0045] (Jewelry Organization) The reasons for limiting the structure of the accessory according to one embodiment of the present invention will be described below. In the following description, "%" means "area %" unless otherwise specified.
[0046] Austenite is 95% or more The austenite content must be 95% or more. If the austenite content is less than 95%, the amount of intermetallic compounds will be excessively large, and the specularity and corrosion resistance of the jewelry will deteriorate. The austenite content is preferably 97% or more, more preferably 98% or more, and even more preferably 99% or more. When the heat treatment of the present invention is carried out, a characteristic structure is produced in addition to the recovery of crystal defects and the generation of annealing twins observed in normal annealing. For example, austenite grains of primary recrystallization that erode prior austenite grains containing twins are observed. Depending on the heat treatment conditions, coarse austenite grains of secondary recrystallization may also be observed. Such structures can be confirmed by using an electron backscatter diffraction (EBSD) device attached to an electron microscope.
[0047] The method for measuring the area percentage of austenite is as follows. First, a backscattered electron image of a scanning electron microscope (SEM-BSE) is used. The measurement magnification is set to a magnification that includes a square with a side length of approximately 710 μm in the observation field, which is the same as the standard diagram described in JIS G0555 Microscopic Test Method for Nonmetallic Inclusions in Steel (2003). For plate material, the measurement location is a position where the center of the plate thickness is parallel to one side (approximately 710 μm) of the square field of view and passes through the center of the square. For bar material, the observation is made at a position where the center of the cross section perpendicular to the longitudinal direction is the center of the square field of view. For plate material and bar material, the highest amount of high Cr, high Mo intermetallic compounds is present at the observation locations mentioned above. On the exposed surface of the jewelry, the area fraction of austenite is higher and the area fraction of intermetallic compounds is lower than at the observation locations mentioned above. In a backscattered electron image, high Cr and high Mo intermetallic compounds appear bright (white) against the contrast of the austenite parent phase, and nonmetallic inclusions appear dark (black). If there is a display of the captured image, adjust it so that the dense part of the compound other than austenite is at the center of the square above. Next, the backscattered electron image photograph is analyzed and classified into three brightness levels: intermetallic compounds (high brightness pixels), austenite (medium brightness pixels), and non-intermetallic compounds (low brightness pixels). The percentage of the number of austenite pixels to the total number of pixels is defined as the austenite area%.
[0048] On the exposed surface of the jewelry, the number of intermetallic compounds having a size of 150 μm or more is zero, and the number of intermetallic compounds having a size of 13 μm or more and less than 150 μm is three or less. In the jewelry according to this embodiment, the number of intermetallic compounds having a size of 150 μm or more on the exposed surface of the jewelry must be zero. If the number of intermetallic compounds having a size of 150 μm or more exceeds zero, the specularity and corrosion resistance of the jewelry will deteriorate. The size of the intermetallic compound is the diameter of the smallest circle that can contain one intermetallic compound inside. The exposed surface of the jewelry is the surface of the jewelry that can be externally observed. In addition, in the jewelry according to this embodiment, the number of intermetallic compounds having a size of 13 μm or more and less than 150 μm on the exposed surface of the jewelry must be 3 or less. If the number of intermetallic compounds having a size of 13 μm or more and less than 150 μm exceeds 3, the specularity and corrosion resistance of the jewelry will deteriorate.
[0049] Since the intermetallic compound is a different phase from the parent phase austenite, the appearance of the intermetallic compound differs from that of the parent phase, and therefore if the number of intermetallic compounds is excessive, sufficient mirror finish for application to jewelry cannot be obtained. In addition, at the interface between the intermetallic compounds and the parent austenite, a region with excessively low Cr and Mo content is formed on the parent phase side. Therefore, if the number of intermetallic compounds is excessive, the corrosion resistance of the jewelry is deteriorated.
[0050] The method for measuring the number of intermetallic compounds with a size of 150 μm or more and intermetallic compounds with a size of 13 μm or more and less than 150 μm is as follows. First, a photograph of the structure of the exposed surface of the jewelry is taken with an optical microscope at a magnification of 10 times. The size of the intermetallic compounds is measured using the photograph. The size of an intermetallic compound is the diameter of the smallest circle that can contain one intermetallic compound inside. Then, the number of intermetallic compounds with a size of 150 μm or more and intermetallic compounds with a size of 13 μm or more and less than 150 μm is counted.
[0051] The average equivalent circle diameter of austenite is 150μm or less The average equivalent circle diameter of the austenite must be 150 μm or less. If the average equivalent circle diameter of the austenite exceeds 150 μm, the specularity of the jewelry deteriorates. The average equivalent circle diameter of the austenite is preferably 70 μm or less.
[0052] The average equivalent circular diameter of austenite is measured as follows. The orientation of each crystal grain is determined using an electron backscattered diffraction (EBSD) device attached to a field emission SEM. A location where the orientation difference between adjacent pixels is 5° or more is defined as a grain boundary. Furthermore, the actual area of the crystal grain is measured, and the average equivalent circular diameter of austenite is calculated using the formula for calculating the area of a circle. Annealing twins present within crystal grains are processed so that they are not determined to be grain boundaries.
[0053] Remainder other than intermetallic compounds and austenite The balance other than the intermetallic compounds and austenite may include non-metallic phases such as inclusions, oxides, nitrides and carbides.
[0054] The accessory according to the present embodiment is not particularly limited, but examples thereof include watch exteriors, necklaces, glasses, etc. Here, the watch exterior is not particularly limited, but examples thereof include watch cases and belts, and cases and belts of wearable devices with a watch function, etc.
[0055] Next, a method for manufacturing an accessory according to an embodiment of the present invention will be described. Note that since the manufacturing method differs depending on whether a plate material is used or a bar material is used, the manufacturing method will be described separately for the case where a plate material is used and the case where a bar material is used.
[0056] A manufacturing method of an ornament according to one embodiment of the present invention includes a step of manufacturing a plate material having the above-mentioned chemical composition, a heat treatment step of heat treating the plate material, and a cold rolling step of plastically processing the plate material.
[0057] (Process for manufacturing board materials) A known method can be used for the process of producing the plate material. The process of producing the plate material is not particularly limited, but for example, the following method can be adopted. In a melting furnace such as a pressurizable electric furnace or a pressurizable high-frequency induction furnace, an alloy having the above-mentioned chemical composition is melted and cast into a steel ingot. The obtained steel ingot is then hot worked to produce a plate material of a desired shape. Then, after the hot working, a solution heat treatment is performed.
[0058] (Heat treatment process) In the heat treatment process, the heat treatment temperature must be 1350 to 1600K. If the heat treatment temperature is less than 1350K, the corrosion resistance and specularity of the jewelry will deteriorate. The heat treatment temperature is preferably 1473K or higher. On the other hand, if the heat treatment temperature is more than 1600K, high-temperature deformation and partial melting will occur due to the weight of the material. The heat treatment temperature is preferably 1548K or lower.
[0059] In the heat treatment step, the heat treatment time needs to satisfy the following formula (2). t dif ≧(6869 / T dif -4.3326) × λ 2 (2). In equation (2), T dif is the heat treatment temperature (K), t dif is the heat treatment time (hours), and λ is the plate thickness (mm). If the heat treatment time does not satisfy formula (2), the amount of intermetallic compounds will be excessively large, and the corrosion resistance and specularity of the jewelry will deteriorate.
[0060] The heat treatment method may be partial heating in an inert gas, which suppresses sublimation of Cr during heat treatment, thereby further improving the corrosion resistance of the jewelry. After the heat treatment step, cooling may be performed at 60° C. / min or more. By cooling at 60° C. / min or more, reprecipitation of intermetallic compounds and an increase in their content are further suppressed, and the corrosion resistance and specularity of the jewelry are further improved.
[0061] (Cold rolling process) In the cold rolling process, the reduction ratio must be 7 to 50%. If the reduction ratio is less than 7%, the average equivalent circle diameter of austenite becomes excessively large, and the specularity of the jewelry deteriorates. The reduction ratio is preferably 13% or more. On the other hand, if the reduction ratio exceeds 50%, the hardness of the material becomes excessively large. As a result, the machinability and pressability of the material deteriorate.
[0062] (Hot forging process and cold forging process) The manufacturing method of the ornament according to one embodiment of the present invention may omit the above-mentioned cold rolling step and have a hot forging step in which the plate material is heated to a temperature in the austenite stable region and plastically deformed in the hot state, and a cold forging step in which plastically deformed in the cold state. The amount of plastic deformation in the hot forging step and the cold forging step is not particularly limited as long as the average circle equivalent diameter of the austenite on the exposed surface of the ornament is 150 μm or less. It is preferable to select the amount of plastic deformation in the hot forging step and the cold forging step so that the average circle equivalent diameter of the austenite on the exposed surface of the ornament is 70 μm or less. The hot forging step and the cold forging step tend to have a higher material yield than the cold rolling step. Therefore, it is preferable to omit the cold rolling step and perform the hot forging step and the cold forging step.
[0063] Next, a manufacturing method of an ornament according to another embodiment of the present invention will be described.
[0064] A method for manufacturing an ornament according to another embodiment of the present invention includes a step of manufacturing a rod stock having the chemical composition described in the above embodiment, a heat treatment step of heat treating the rod stock, and a cold wire drawing step of plastically processing the rod stock.
[0065] (Rod manufacturing process) The rod can be manufactured by a known method.
[0066] (Heat treatment process) In the heat treatment process, the heat treatment temperature must be 1350 to 1600K. If the heat treatment temperature is less than 1350K, the amount of intermetallic compounds becomes excessively large, and the corrosion resistance and specularity of the jewelry deteriorate. The heat treatment temperature is preferably 1473K or more. On the other hand, if the heat treatment temperature is more than 1600K, high-temperature deformation and partial melting occur due to the weight of the material. The heat treatment temperature is preferably 1548K or less.
[0067] In the heat treatment step, the heat treatment time needs to satisfy the following formula (3). t dif ≧(6869 / T dif-4.3326) × d (3). In equation (3), T dif is the heat treatment temperature (K), t dif is the heat treatment time (hours), and d is the equivalent circle diameter (mm) of the bar. If the heat treatment time does not satisfy formula (3), the amount of intermetallic compounds will be excessively large, and the corrosion resistance and specularity of the jewelry will deteriorate.
[0068] The concentration diffusion of Cr and Mo in high Cr-high Mo intermetallic compounds during heat treatment proceeds one-dimensionally from the center plane in the thickness direction to both rolling surfaces in plate material, while it proceeds two-dimensionally from the center axis in the wire drawing direction to the circumferential side surfaces in bar material. In the equation (2) for the heat treatment time of the plate material, the time when the amount of diffusion from the high Cr high Mo intermetallic compound to the surrounding austenite becomes equivalent in the plate material and the bar material is assumed. 2 By replacing with the diameter d, equation (3) is derived.
[0069] As for the conditions other than the heat treatment temperature and heat treatment time, the conditions described in the manufacturing method of the accessory according to the previous embodiment can be adopted.
[0070] (Cold wire drawing process) In the cold wire drawing process, the reduction in area must be 7 to 50%. If the reduction in area is less than 7%, the average equivalent circle diameter of austenite becomes excessively large, and the specularity of the jewelry deteriorates. The reduction in area is preferably 13% or more. On the other hand, if the reduction in area is more than 50%, the hardness of the material becomes excessively large. As a result, the machinability and pressability of the material deteriorate.
[0071] As for the conditions other than the area reduction rate, the conditions described in the manufacturing method of the accessory according to the previous embodiment can be adopted.
[0072] (Hot forging process and cold forging process) The manufacturing method of the ornament according to another embodiment of the present invention may omit the above-mentioned cold wire drawing step and have a hot forging step in which the bar material is heated to a temperature in the austenite stable region and plastically deformed in the hot state and a cold forging step in which plastically deformed in the cold state. The amount of plastic deformation in the hot forging step and the cold forging step is not particularly limited as long as the average circle equivalent diameter of the austenite on the exposed surface of the ornament is 150 μm or less. It is preferable to select the amount of plastic deformation in the hot forging step and the cold forging step so that the average circle equivalent diameter of the austenite on the exposed surface of the ornament is 70 μm or less. The hot forging step and the cold forging step have a higher material yield than the cold wire drawing step. Therefore, it is preferable to omit the cold wire drawing step and perform the hot forging step and the cold forging step.
[0073] The manufacturing method of the ornament according to the embodiment of the present invention described above may include a manufacturing process for giving the ornament a predetermined shape and appearance. The manufacturing process for giving the ornament a predetermined shape and appearance may be a known manufacturing method.
[0074] Although not limited to this, a method for manufacturing a watch exterior will be described as an example. First, a method for manufacturing a watch case, which is one of the watch exteriors, will be described.
[0075] (Watch case manufacturing method) A blank is punched out from the plate material or bar material (hereinafter sometimes referred to as "material") that has been subjected to the above-mentioned heat treatment process and cold rolling process or cold wire drawing process using a crank press machine and a punching die. The punched blank is formed into a near-net shape using multiple forming dies. If the material hardens during the process, an annealing process is appropriately performed in which the material is heated to a solution temperature or higher in a bright annealing furnace and quenched.
[0076] A method for manufacturing a blank that employs a hot forging process and a cold forging process, separate from the above, will be described. First, the plate or bar material that has been subjected to the above-mentioned heat treatment process is heated by high-frequency induction heating or a heating furnace, and is hot forged into a shape similar to the above-mentioned blank using a press and a plurality of heat-resistant dies. After removing the oxide film on the surface by pickling or sandblasting, a near-net-shape blank is produced in the cold using a press and a forming die. Intermediate annealing may be performed as appropriate during the hot forging process and the cold forging process. It is preferable to reduce the number of dies in the hot forging step and increase the number of dies in the cold forging step, which can further reduce the average equivalent circle diameter of austenite.
[0077] The pressed blank then goes through multiple cutting and drilling processes on a numerically controlled (NC) lathe to turn the inner diameter, which is the standard for processing, cut the surface of the pressed surface, drill holes for attaching the band and the winding stem, and process the screws to attach the back cover, before being transformed into an unpolished watch case.
[0078] The unpolished watch case is roughly polished using a Zaratsu polishing machine with waterproof abrasive paper of #360, #800, #1200, and #2000 attached.The waterproof abrasive paper is then replaced with an abrasive cloth, and the finish polishing is performed using alumina abrasives with grain sizes of 3μm, 1μm, 0.3μm, and 0.05μm.
[0079] After the final polishing, the watch is polished with a buff to give it a glossy finish. Depending on the design of the watch exterior, a mask may be applied and then creased with a rotating wire brush or decorated with a honing (sandblast) process. The winding stem pipe to which the crown is attached is brazed or glued, and the case is complete. The back cover and glass edge are also created using the same process.
[0080] Next, a method for manufacturing the metal band of the watch exterior will be described. (Metal Band Manufacturing Method) The material that has been subjected to the above-mentioned heat treatment process and cold rolling or cold wire drawing process is pressed to punch out the links in a press, just like a watch case, and then the links are shaped to a shape close to the finished product in a molding press.Then, the surface is machined, and the pin holes that connect the links are drilled and polished.Finally, the links are connected in the specified order with C-ring pins or the like, and a clasp is attached for attachment and removal.
[0081] The manufacturing method for the watch exterior is not limited to the method described above, and any manufacturing method that is commonly used in the manufacture of watch exteriors may be used. EXAMPLES
[0082] Next, an embodiment of the present invention will be described. The conditions shown in the embodiment are an example adopted to confirm the feasibility and effects of the present invention. Therefore, the present invention is not limited to this example. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and the object of the present invention is achieved.
[0083] (Heat treatment conditions) Steel types A to D were prepared, each having the chemical composition shown in Table 1. Steel type A, having a plate thickness of 6 mm to 22 mm, was heat treated under the conditions shown in Table 2, and the material was quenched after the heat treatment. For the material after the heat treatment, the number of intermetallic compounds having a size of 150 μm or more and intermetallic compounds having a size of 13 μm or more and less than 150 μm was measured.
[0084] The method for measuring the composition of the materials was as follows. For elements other than N, samples were first taken from the 1 / 4 thickness part of the plate material. The composition was then measured in accordance with JIS G 1256 (method for fluorescent X-ray analysis of iron and steel) in 2013. The N content of the above samples was measured using JIS G 1228 (iron and steel - nitrogen determination method) in 2006.
[0085] The method for measuring the number of intermetallic compounds having a size of 150 μm or more and intermetallic compounds having a size of 13 μm or more and less than 150 μm was as follows. First, a photograph of the structure in the center of the plate thickness was taken at a magnification of 10 times using an optical microscope. The size of the intermetallic compounds was measured using the photograph. The size of the intermetallic compound is the diameter of a circle with the smallest area that can contain one intermetallic compound inside. Then, the number of intermetallic compounds having a size of 150 μm or more and intermetallic compounds having a size of 13 μm or more and less than 150 μm was counted. In the plate material, the high Cr and high Mo intermetallic compounds are most abundant in the center of the plate thickness. Therefore, the number of intermetallic compounds measured by the above method was assumed to be the number of intermetallic compounds having a size of 150 μm or more and intermetallic compounds having a size of 13 μm or more and less than 150 μm. In addition, since the cold rolling process is performed at room temperature, the number of intermetallic compounds in the material does not change substantially. For intermetallic compounds having a size of 150 μm or more, the measurement was terminated when the number of particles was 1. For intermetallic compounds having a size of 13 μm or more and less than 150 μm, the measurement was terminated when the number of particles was 4. The measurement results for the number of intermetallic compounds having a size of 13 μm or more and less than 150 μm are shown in Table 2. In Table 2, all materials in which the number of intermetallic compounds having a size of 13 μm or more and less than 150 μm was 0 also had 0 intermetallic compounds having a size of 150 μm or more.
[0086] The method for measuring the area percentage of austenite was as follows. First, backscattered electron images were taken with a scanning electron microscope (SEM-BSE). The measurement magnification was set to a magnification that included a square with sides of approximately 710 μm in the observation field, which is the same as the standard diagram described in JIS G0555 Microscopic Test Method for Nonmetallic Inclusions in Steel (2003). The measurement location was a position where the center of the plate thickness was parallel to one side of the square field of view (approximately 710 μm) and passed through the center of the square. Next, the backscattered electron image photograph is analyzed and classified into three brightness levels: intermetallic compounds (high brightness pixels), austenite (medium brightness pixels), and non-intermetallic compounds (low brightness pixels). The percentage of the number of austenite pixels to the total number of pixels is defined as the austenite area %. In addition, since the cold rolling process is performed at room temperature, the austenite area % of the material does not change substantially. Therefore, the austenite area % of the material after the heat treatment process was assumed to be the austenite area % of the jewelry. The measurement results of the austenite area % are shown in Table 3.
[0087] [Table 1]
[0088] [Table 2]
[0089] [Table 3]
[0090] As shown in Tables 2 and 3, when the heat treatment conditions in the heat treatment process satisfied the following formula (2), the area percentage of austenite and the number of intermetallic compounds having a size of 150 μm or more and intermetallic compounds having a size of 13 μm or more and less than 150 μm fell within the range of the present invention. The area percentage of austenite was 95% or more under all conditions. The remainder of the structure was a nonmetallic phase. t dif ≧(6869 / T dif -4.3326) × λ 2 (2). In equation (2), T dif is the heat treatment temperature (K), t dif represents the heat treatment time (hours), and λ represents the thickness of the plate material (mm).
[0091] (Cold rolling conditions) A 6 mm thick plate of steel type A was heat treated at 1473K for 12 hours. After heat treatment, it was cold rolled to the specified thickness using a two-stage rolling mill. The reduction in one pass was 0.10 mm, and rolling was completed when the specified thickness was reached. The cold rolling reduction is shown in Table 4.
[0092] The rolled material was cut out on a plane perpendicular to the rolling direction. A blank was punched out from the cut out material using a crank press and a punching die. The punched blank was molded into a near-net shape using multiple forming dies. The pressed blank is then subjected to multiple cutting and drilling processes on a numerically controlled (NC) lathe, including inner diameter turning, which is the standard for processing, surface cutting of the pressed surface, drilling sharp holes for attaching the band and lug holes, and threading for attaching the back cover, to obtain an unpolished watch case.
[0093] The unpolished watch case was roughly polished using a Zaratsu polishing machine with waterproof abrasive paper of #360, #800, #1200 and #2000 attached. The waterproof abrasive paper was then replaced with an abrasive cloth, and finish polishing was performed using alumina abrasives with grain sizes of 3μm, 1μm, 0.3μm and 0.05μm. After the finish polishing, buff polishing was performed to add luster.
[0094] As a result, watch cases of Examples 1 to 6 and Comparative Examples 1 to 4 were obtained. The hardness of the material was measured immediately after cold rolling. A Vickers hardness tester was used for the hardness measurement. The load during hardness measurement was 0.3 kgf, and the holding time was 15 seconds. The measurement results using the Vickers hardness tester are shown in Table 4.
[0095] The average equivalent circular diameter of austenite crystal grains was determined as follows. The orientation of each crystal grain was determined using an electron backscattered diffraction (EBSD) device attached to a field emission SEM. A location where the orientation difference between adjacent pixels was 5 degrees or more was defined as a grain boundary. In addition, the actual area of the crystal grains was measured, and the average equivalent circular diameter of austenite was calculated using the formula for determining the area of a circle. Note that a process was performed in which annealing twins present within crystal grains were not determined to be grain boundaries. The measurement results of the average equivalent circular diameter of austenite are shown in Table 4.
[0096] The specularity of the watch case was measured by visually judging it. The specularity was evaluated on a three-level scale: poor, average, and good. The results of the specularity measurements are shown in Table 4.
[0097] [Table 4]
[0098] In Examples 1 to 6, the heat treatment conditions in the heat treatment process and the rolling reduction rate in the cold rolling were within the ranges of the present invention, so the material did not become excessively hard. Therefore, even after the cold rolling process, the material had sufficient workability. In addition, the average equivalent circular diameter of austenite did not become excessively large, so the mirror surface of the watch case was sufficient.
[0099] On the other hand, in Comparative Examples 1 to 3, the cold rolling reduction was insufficient, so the mirror surface properties of the watch cases were insufficient, and in Comparative Example 4, the cold rolling reduction was excessive, so the workability of the material after the cold rolling process was insufficient.
[0100] (Corrosion resistance) In Example 7, a test piece for a corrosion resistance test was prepared as follows. A 2 mm thick plate of steel type B was heat treated at 1473K for 1.5 hours. After heat treatment, the plate was quenched. The plate was then cold rolled at a rolling reduction of 25%. The thickness of the plate after cold rolling was 1.5 mm. The cold rolled plate was cut into a rectangle of 20 mm high x 40 mm wide. After the corners were chamfered, the rolled surfaces (2 surfaces) and the cut side surfaces (4 surfaces) were polished in the same manner as in the manufacturing method of the watch case in Example 1, and were finished to a mirror finish. In Comparative Examples 5 to 7, neither heat treatment nor cold rolling was performed. Test pieces for the corrosion resistance test were prepared in the same manner as in Example 7.
[0101] The corrosion resistance test was carried out as follows. Ten mirror-finished rectangular test pieces were subjected to a half-immersion test in saturated salt water at 60°C. Specifically, saturated salt water coexisting with solid salt was placed in a container, and the test pieces were set on a polytetrafluoroethylene rack that could be tilted at 30 degrees from the vertical and submerged in the container. The amount of liquid was then adjusted so that the test pieces were immersed in the salt water up to a height of 10 mm. The container was left to stand in a thermostatic bath at 60°C. The test pieces were periodically removed and washed, and the occurrence of pitting corrosion and intergranular corrosion was confirmed with a stereomicroscope. The half-immersion test was carried out for a maximum of 1000 hours. The corrosion time was the average time until corrosion occurred for the 10 test pieces. The corrosion time for test pieces that did not corrode after 1000 hours was 1000 hours. The corrosion resistance test results are shown in Table 5.
[0102] [Table 5]
[0103] Example 7 showed good corrosion resistance since the heat treatment conditions and PRE were within the range of the present invention. In Comparative Example 5, the heat treatment conditions were outside the range of the present invention, and therefore the corrosion resistance was inferior to that of Example 7. In Comparative Examples 6 and 7, the heat treatment conditions and PRE were outside the range of the present invention, and therefore the corrosion resistance was insufficient.
[0104] (When cold forging and hot forging processes are performed) Tests were also conducted in the case where the cold rolling process and the cold wire drawing process were omitted and only the hot forging process and the cold forging process were performed.
[0105] In Example 8, a round bar of steel type A with an average circular diameter of 25 mm was used. The round bar was heat treated in an argon atmosphere at 1523 K for 8 hours. After the heat treatment, the round bar was quenched with pressurized nitrogen gas. The heat-treated round bar was cut into a length of about 40 mm to form a billet. The billet was heated to 1473 K using a high-frequency induction heating method, and the billet was punched using multiple heat-resistant forging dies and hot forged into a shape close to the blank. After hot forging, the oxide film on the surface was removed by sandblasting or acid washing, and then cold forging was performed. Thereafter, a watch case was obtained by the same process as in Examples 1 to 7.
[0106] In Example 9, a plate material of steel type A having a thickness of 14 mm and a width of 40 mm was used. The heat treatment conditions in Example 9 were 1523 K and 36 hours. The heat-treated plate material was cut to a length of approximately 35 mm. Thereafter, a watch case was obtained under the same conditions as in Example 8.
[0107] The average equivalent circular diameter and specularity of the austenite of Examples 8 and 9 were measured by the same methods as in Examples 1 to 7. As a result, the average equivalent circular diameter of the austenite of Examples 8 and 9 was both 150 μm or less, and the specularity was also sufficient. [Industrial Applicability]
[0108] As described above, according to the present invention, it is possible to provide an ornament having excellent corrosion resistance and specular surface properties and a manufacturing method thereof, and thus the present invention has high industrial applicability.
Claims
1. Chemical composition, by mass%, C: 0.10% or less, Si: 1.5% or less, Mn: 1.5% or less, P: 0.050% or less, S: 0.050% or less, O: 0.020% or less, Ni: 15.0 to 38.0%, Cr: 17.0-27.0%, Mo: 4.0 to 8.0%, and N: 0.55% or less; The balance is Fe and impurities. The structure is austenite at 95% or more by area percent, When the diameter of a circle having the smallest area capable of containing one intermetallic compound therein is defined as the size of the intermetallic compound, the number of the intermetallic compounds having a size of 150 μm or more on the exposed surface of the jewelry is 0, and the number of the intermetallic compounds having a size of 13 μm or more and less than 150 μm is 3 or less, The average equivalent circular diameter of the austenite is 150 μm or less, The PRE defined by the following formula (1) is 40 or more. An ornament characterized by the above. PRE=[Cr]+3.3[Mo]+16[N]...(1) In the formula (1), [Cr], [Mo], and [N] represent the mass % contents of Cr, Mo, and N in the composition of the jewelry, and 0 is substituted if these elements are not contained.
2. The jewelry is a watch case.
2. The accessory according to claim 1.
3. A method for manufacturing the accessory according to claim 1 or 2, comprising: A step of manufacturing a plate material; A heat treatment step of heat treating the plate material; A cold rolling process for plastically processing the plate material, In the heat treatment step, the heat treatment temperature is 1350 to 1600K, In the cold rolling process, the reduction ratio is 7 to 50%. A method for manufacturing a personal accessory, comprising the steps of:
4. A method for manufacturing the accessory according to claim 1 or 2, comprising the steps of: Manufacturing a bar stock; a heat treatment step of heat treating the bar material; a hot forging step of hot forging the bar; A cold forging process for cold forging the bar material forged by the hot forging. In the heat treatment process, the heat treatment temperature is 1350 to 1600K. A method for manufacturing a personal accessory, comprising the steps of:
5. A method for manufacturing the accessory according to claim 1 or 2, comprising the steps of: A step of manufacturing a plate material; A heat treatment step of heat treating the plate material; A cold rolling process for plastically processing the plate material, In the heat treatment step, the heat treatment temperature is 1350 to 1600K, and the heat treatment time satisfies the following formula (2): In the cold rolling process, the reduction ratio is 7 to 50%. A method for manufacturing a personal accessory, comprising the steps of: t dif ≧(6869 / T dif -4.3326)×λ 2 ・・・(2) However, in formula (2), T dif is the heat treatment temperature (K), t dif represents the heat treatment time (hours), and λ represents the thickness of the plate material (mm).
6. A method for manufacturing the accessory according to claim 1 or 2, comprising the steps of: A step of manufacturing a plate material; A heat treatment step of heat treating the plate material; a hot forging process for hot forging the plate material; A cold forging process for cold forging the plate material. In the heat treatment process, the heat treatment temperature is 1350 to 1600K, and the heat treatment time satisfies formula (2). A method for manufacturing a personal accessory, comprising the steps of: t dif ≧(6869 / T dif -4.3326)×λ 2 ・・・(2) However, in formula (2), T dif is the heat treatment temperature (K), t dif represents the heat treatment time (hours), and λ represents the thickness of the plate material (mm).
Citation Information
Patent Citations
Production of external parts for hard portable timepiece
JP1988125616A
Mo-containing high cr high ni austenitic stainless steel plate having excellent ductility and production method therefor
JP2002322545A
Wire rod of nonmagnetic sulfur free-cutting stainless steel superior in cold drawability and corrosion resistance
JP2004307977A
Stainless steel sheet for solid high polymer type fuel cell separator, its production method, and its forming method
JP2004339569A
Alloy for accessory
JP2012050649A
